Hard-to-treat or hard-to-catch? Clinical features and therapeutic outcomes of help-seeking foster care youths with mood disorders - Benarous, Xavier; Lahaye, Hélène; Pellerin, Hugues; Consoli, Angèle; Cohen, David; Labelle, Réal; Renaud, Johanne; Gérardin, Priscille; El-Khoury, Fabienne; van der Waerden, Judith; Guilé, Jean-Marc (Frontiers in Psychiatry, 2023)
The high level of emotional problems in youths placed in foster care contrasts with the limited use of evidence-based treatments. This study aims to better characterize the clinical features and therapeutic outcomes of foster care youths with mood disorders. A secondary analysis of data collected in the context of a French-Canadian clinical research network on pediatric mood disorders in four sites was conducted to compare three groups of patients with depressive or bipolar disorder : those without exposure to child welfare intervention (WCWI, n=181), those who received non-placement psychosocial intervention (NPI, n=62) and those in placement interventions (PI, n=41). We observed a very high rate of academic problems in patients in the groups NPI/PI compared to those in the WCWI group. Patients in the PI group had more disruptive behavioral disorders (OR=6.87, 95% CI [3.25-14.52]), trauma-related disorders (OR=3.78, 95% CI [1.6-8.94]), and any neurodevelopmental disorders (OR=2.73, 95% CI [1.36-5.49]) compared to the other groups (NPI/WCWI). Among inpatients, the Clinical Global Impression-Improvement scale and the change in the Children Global Assessment Scale during the hospital stay did not differ across the three groups. We observed a higher prescription rate of antipsychotics in the PI group compared to the NPI/WCWI groups, but no significant difference for antidepressants and mood stabilizers. These findings support the view that, when provided with dedicated support, fostered inpatient youths can improve in a range comparable to other inpatients. Undetected neurodevelopmental disorders and academic problems are likely important contributors of the burden of mood disorders in these youths.